Pengaruh Persepsi Nilai Terhadap Kepuasan Wisatawan Pada Kebun Raya Mangrove (KRM) Surabaya - Dwi Suryaning Endah Yanie; Sanaji Sanaji; Yessy Artanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Nature tourism is a tourist attraction in East Java with the number of visits increasing significantly from 2019 to 2023. Surabaya has a new natural tourist spot that was inaugurated in July 2023, namely the Surabaya Mangrove Botanical Garden (KRM). KRM Surabaya has a contribution in preserving the environment, providing education to the community and increasing Surabaya City's Original Revenue. Over time, the level of tourist visits to KRM Surabaya has decreased. This study aims to analyze the effect of perceived value on tourist satisfaction. This study uses a conclusive research design with a cross-sectional approach. Data were collected through a closed questionnaire from tourists who had visited KRM Surabaya. Data analysis was performed using the PLS-SEM method. The results showed that perceived value has a moderate influence on tourist satisfaction.